NanoTips for Using Mindfulness Strategies to Build Resilience with Gemma Leigh Roberts. - Gemma Leigh Roberts, Dr (linkedin.com, 2024)
Discover ways to use mindfulness techniques to build everyday resilience. Each video is less than three minutes long, so you can make learning fit into even your busiest days.